Occupational resource profiles for an addressee orientation in occupational health management: a segmentation analysis - Friedrich, Julian; Münch, Anne-Kristin; Thiel, Ansgar; Voelter-Mahlknecht, Susanne; Sudeck, Gorden (Frontiers in Psychology, 2023)
In order to make sustainable decisions in precision prevention and health promotion, it is important to adequately assess people's demands and resources at work. To reach them in an addressee-oriented way, a segmentation of employers and employees based on occupational resources is a promising option. We identified profiles based on personal and perceived organizational resources. Further, we used job demands for profile description to get a deeper understanding of the profiles characterizing people with similar occupational resources.Personal occupational resources (occupational health literacy and self-efficacy) and perceived organizational resources (job decision latitude and participation in health at work) were assessed among employers and employees (n = 828) in small and medium-sized enterprises in Germany. Job demands, socioeconomic status and hierarchy levels in the company were used for further profile descriptions.A six-profile solution fitted best to the data based on cluster and profile analyses. One profile was characterized by above-average occupational resources, another profile by below-average resources. The other four profiles showed that the individual and perceived organizational resources contrasted. Either organizational resources such as job decision latitude existed and personal resources were not highly developed, or people had high individual motivation, but few possibilities to participate in health at work. People with medium or high job demands as well as people with low socioeconomic status occurred most frequently in below-average resource profiles. Employers with high hierarchy levels were overrepresented in the above-average profiles with high organizational resources.Following the segmentation of the addressees, organizations might be supported in identifying needs and areas for prevention and health promotion. Interventions can be optimally developed, tailored and coordinated through a deeper understanding of job demands and resources. Especially employees with low socioeconomic status and high job demands might profit from an addressee-orientated approach based on resource profiles. For example, employees obtain an overview of their occupational resource profile to recognize development potential for safe and healthy behavior at work. Follow-up research should be used to examine how this feedback to employers and employees is implemented and how it affects the sustainability of tailored interventions.